Densely populated single‐atom catalysts for boosting hydrogen generation from formic acid - Xiaogeng Zhao; Junmin Wang; Dongnuan Zhang; Yunhui Hao; Xingmian Zhang; Junna Feng; Hong Su; Cheng Feng; Chun Wang (Carbon Energy)
Abstract The single‐atom M‐N‐C (M typically being Co or Fe) is a prominent material with exceptional reactivity in areas of catalysis for sustainable energy. However, the formation of metal nanoparticles in M‐N‐C materials is coupled with high‐temperature calcination conditions, limiting the density of M‐Nx active sites and thus restricting the catalytic performance of such catalysts. Herein, we describe an effective decoupling strategy to construct high‐density M‐Nx active sites by generating polyfurfuryl alcohol in the MOF precursor, effectively preventing the formation of metal nanoparticles even with up to 6.377% cobalt loading. This catalyst showed a high H2 production rate of 778 mL gcat−1 h−1 when used in the dehydrogenation reaction of formic acid. In addition to the high density of the active site, a curved carbon surface in the structure is also thought to be the reason for the high performance of the catalyst.